HALAL CULINARY INDUSTRY 2026 TO SUPPORT THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN SUPPORTING THE PERSPECTIVE OF THE HALAL INDUSTRY MAQASHID SYARI'AH - Syahbudi, Muhammad; Irham, Mawaddah; Indra, Ahmad Perdana (Strategic Management Business Journal, 2025)
Research background: The growth of the halal culinary industry continues to grow both domestically and globally. The halal industry, which includes goods and services, has its own attraction for many players and is in line with the Government's target by 2026 by increasing the halal culinary industry in Indonesia by going through several changes starting from the Halal Certification Obligations. Halal consumption patterns are not only a concern for Muslims but also many parties, so that the halal culinary industry can play a role in the economy. Purpose of the article: The purpose of this research is to identify the development of the halal culinary industry and describe the role of the halal industry in supporting the SDGs agenda towards the 2026 halal industry. Methods: The method used in this study is qualitative, with a literature study research approach, from several sources that are considered relevant to the research theme. The data source used is secondary data. The data collection technique is literature, and the data analysis technique used is qualitative descriptive. The role of the halal industry in realizing the SDGs is; Reducing poverty, reducing hunger, healthy living and well-being, decent work and economic growth, innovation industries and infrastructure. Responsible consumption and production. And partnerships to achieve goals.